IMPACT OF THE TYPE OF A BASIC THERAPY ON THE QUALITY OF LIFE IN CHILDREN WITH CONTROLLED MODERATELY SEVERE BRONCHIAL ASTHMA - S.V. Bychkovskaya; N.A. Il'enkova; S.Yu. Tereschenko (Педиатрическая фармакология, 2010)
The article provides results of a study for the impact of low doses fluticasone propionate and sodium nedocromil on the quality of life in children with bronchial asthma. It evidences Statistically valid improvements in the quality of life are identified and achieved control over the disease (90%) in a group of patients that were administered fluticasone propionate. A group of patients that were administered sodium nedocromil, did not show statistically valid improvements in the quality of life and control was maintained only in 62% of the patients. Key words: bronchial asthma, treatment, quality of life, fluticasone propionate, sodium nedocromil, children. (Pediatric Pharmacology. – 2010; 7(2):60-64)